2022
DOI: 10.1002/jmri.28525
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Quadriceps Femoris Muscle Function and MRI‐Derived Water Diffusion and Adipose Tissue Measurements in Young Healthy Males

Abstract: Background Water diffusion and adipose tissue in a muscle can be evaluated by MRI. However, determining which quadriceps femoris muscle (QM) characteristics independently predict peak knee extension torque during maximum voluntary isometric contractions (MVICs), individual muscle activity during MVICs and sit‐to‐stand transitions is unknown. Purpose To determine which QM characteristics predict knee extension muscle strength and individual muscle activity. Study Type Prospective, cross‐sectional. Subjects A to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
(65 reference statements)
0
3
0
Order By: Relevance
“…In this issue of JMRI, a study by Yamauchi and colleagues investigated 20 healthy males (aged 22-40 years) with a physical activity level <1 hour/week, to determine which quadriceps femoris muscle (QM) characteristics predict knee extension muscle strength and individual muscle activity. 9 This study demonstrated that a lower RF λ1 value, rather than total muscle activity, predicted greater peak knee extension torque. Moreover, the VM muscle activity ratio during knee extension MVIC and sit-to-stand transition decreased as the VM MAT percentage increased, whereas higher VM: QM λ1 ratio exhibited higher VM muscle activity ratio during sit-to-stand transitions.…”
mentioning
confidence: 61%
See 1 more Smart Citation
“…In this issue of JMRI, a study by Yamauchi and colleagues investigated 20 healthy males (aged 22-40 years) with a physical activity level <1 hour/week, to determine which quadriceps femoris muscle (QM) characteristics predict knee extension muscle strength and individual muscle activity. 9 This study demonstrated that a lower RF λ1 value, rather than total muscle activity, predicted greater peak knee extension torque. Moreover, the VM muscle activity ratio during knee extension MVIC and sit-to-stand transition decreased as the VM MAT percentage increased, whereas higher VM: QM λ1 ratio exhibited higher VM muscle activity ratio during sit-to-stand transitions.…”
mentioning
confidence: 61%
“…In this issue of JMRI , a study by Yamauchi and colleagues investigated 20 healthy males (aged 22–40 years) with a physical activity level <1 hour/week, to determine which quadriceps femoris muscle (QM) characteristics predict knee extension muscle strength and individual muscle activity 9 . This study demonstrated that a lower RF λ1 value, rather than total muscle activity, predicted greater peak knee extension torque.…”
mentioning
confidence: 99%
“…Takao et al [23] found a positive correlation of the soleus muscle in the non-contraction state between the maximum power and the AD, λ2, and MD. However, The study of Yamauchi et al [24] showed that a lower rectus femoris AD value predicted greater peak knee extension torque, which may lead to the fact that the rectus femoris is a biarticular muscle and includes the highest proportion of fast fiber type. AD was also found associated with fiber size, edema, and fibrosis [14] .…”
Section: Subjects and Methods Ethical Approvalmentioning
confidence: 99%
“…Examples in addition to myopathies discussed above are changes in muscle diffusivity associated with denervation [ 94 ], metabolic disease [ 95 , 96 ] muscle fiber tears [ 97 , 98 ], and differences in muscle diffusivity between osteoporotic and osteoarthritic subjects [ 99 ]. Another interesting field is the relation between muscle properties and external muscle strength that has important implications for optimizing training effects in athletes and for exercise or pharmaceutical interventions in sarcopenia and frailty [ [100] , [101] , [102] , [103] , [104] , [105] , [106] ].…”
Section: Mr Imagingmentioning
confidence: 99%